Methodology for Analyzing Road Safety in the Vicinity of Trip-Generating Centers - Santos, Janekelly Vilela; Silva, Philippe Barbosa (National Journal of City Management, 2026)
Objective – To develop an instrument for Road Safety (RS) analysis in the vicinity of Trip Generators (TGs), aiming to assess the impacts of these developments on the safety of the urban road system.Methodology – Based on a literature review, it was possible to select similar existing instruments, compile information, analyze relevant aspects, and develop the methodology for RS inspection. Initially, the six selected references resulted in 467 observational analysis parameters, which served as the technical basis for creating the 10 analysis items that comprise the checklist with 24 aspects to be verified. The developed checklist is accompanied by its Practical Guide for Application and Indicator Calculation, favoring the application and quality of the obtained results.Originality/Relevance – The study fills an important gap in the area of urban road safety, given the lack of specific instruments applicable to the Brazilian urban context, especially in the areas of influence of TGs. Brazilian cities face growing problems related to ineffective urban mobility and low levels of road safety, externalities associated with population growth and urban development, a context in which TGs can significantly aggravate the risks of traffic crashes.Results – A structured checklist was developed with 10 analysis items and 24 aspects to be verified, accompanied by a Practical Guide for Application and Indicator Calculation. The instrument not only verifies the compliance of each item but also numerically estimates the level of adherence to the criteria through a system of indicators, weights, and a general road safety assessment index.Theoretical/Methodological Contributions – The developed instrument represents a methodological advancement by offering a systematic, practical, and quantitative approach to road safety analysis in urban areas influenced by TGs. The tool distinguishes itself by combining simplicity in data collection with rigor in evaluation, enabling not only qualitative diagnoses but also the objective measurement of road safety levels through weighted indicators.Social and Environmental Contributions – It is expected that the use of the instrument will contribute to the reduction of traffic crashes and their social consequences, including fatalities, injuries, and economic impacts on public health. The tool can support more assertive strategies and decision-making by public managers, technicians, and developers in promoting road safety, favoring sustainable urban planning and the construction of safer cities for all road system users.
Keywords: Road safety; Trip Generators; Road safety inspection